From the shop to the drain — Volatile methylsiloxanes in cosmetics and personal care products. (July 2016) - Capela, Daniela; Alves, Arminda; Homem, Vera; Santos, Lúcia
Abstract: Organosiloxanes are widely used in the formulation of a broad range of cosmetic and personal care products (PCPs), including creams and lotions, bath soaps, shampoo and hair care products to soften, smooth, and moisten. In fact, the intensive and widespread use of organosiloxanes combined with their lipophilic nature, makes them interesting targets for future research, particularly in the toxicology area. This study focused on determining the concentration levels of these compounds in the bestselling brands of PCPs in the Oporto region (Portugal), allowing the estimation of dermal and inhalation exposure to siloxanes and the evaluation of the quantities released to the environment "down-the-drain" and to air. To accomplish this task, a QuEChERS technique ("Quick, Easy, Cheap, Effective, Rugged, and Safe") was employed to extract the siloxanes from the target PCPs, which has never been tested before. The resulting extract was analysed by gas chromatography–mass spectrometry (GC–MS). The limits of detection varied between 0.17 (L2) and 3.75 ng g − 1 (L5), being much lower than any values reported in the literature for this kind of products. In general, satisfactory precision (< 10%) and accuracy values (average recovery of 84%) were obtained. 123 PCPs were analysed (moisturizers, deodorants, body and hair washes, toilet soaps, toothpastes and shaving products) and volatile methylsiloxanes were detected in 96% of the samples, in concentrations between 0.003 μg g − 1 and 1203 μg g − 1 . Shampoo exhibited the highest concentration for cyclic and aftershaves for linear siloxanes. Combining these results with the daily usage amounts, an average daily dermal exposure of 25.04 μg kgbw − 1 day − 1 for adults and 0.35 μg kgbw − 1 day − 1 for baby/children was estimated. The main contributors for adult dermal exposure were body moisturizers, followed by facial creams and aftershaves, while for babies/children were body moisturizers, followed by shower gel and shampoo. Similarly, the average daily inhalation exposure was also estimated. Values of 1.56 μg kgbw − 1 day − 1 for adults and 0.03 μg kgbw − 1 day − 1 for babies/children were calculated. An estimate of the siloxanes amount released "down-the-drain" into the sewage systems through the use of toiletries was also performed. An emission per capita between 49.25 and 9574 μg day − 1 (mean: 1817 μg day − 1 ) is expected and shampoo and shower gel presented the higher mean total values (1008 μg day − 1 and 473.3 μg day − 1, respectively). In the worst-case scenario, D5 and D3 were the predominant siloxanes in the effluents with 3336 μg day − 1 and 3789 μg day − 1, respectively. Regarding the air emissions per capita, values between 8.33 and 6109 μg day − 1 (mean: 1607 μg day − 1 ) are expected and D5 and D6 were the predominant siloxanes. Highlights: Siloxanes were detected in adult and baby/children products (0.003–1203 μg g − 1 ). Higher concentrations of total siloxanes were detected in moisturizers. Dermal exposure was 25 and 0.4 μg kgbw − 1 day − 1 for adults and babies, respectively. Inhalation exposure dose to siloxanes ranged from 0.03 to 5.94 μg kgbw − 1 day − 1 . Down-the-drain and air emissions of 1817 and 1607 μg day − 1 per capita were found.